PENGARUH BEBERAPA BAHAN ORGANIK TERHADAP MAKROFAUNA TANAH DAN PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Dian Wahyudi Eka Putra; Wardati '; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Palm oil (Elaeis guineensis Jacq.) is a plantation commodity which plays important role in economics of Indonesia. Palm oil can grow at various ground type by paying attention to the soil characteristics including soil biology. Soil biology like existence of soil macrofauna depend on availibility of energy such as organic matter and decomposed it, so that can maintain the soil productivity. This research aims to determine the effect of organic matters and to determine the better of organic matters for soil macrofauna and palm oil growth. This research has been conducted at the experimental farm of Agricultural Faculty Riau University on May to August 2015. This research was carried out experimentally by using randomized block design (RBD) with 4 treatments (without organic matter, palm oil empty fruit bunch, sawdust and congongrass of 10 kg/plant) and 6 replications, so there are 24 experimental units.The data obtained were analyzed using ANOVA and followed by further test DNMRT at 5% level. The result showed that the application of 10 kg/plant sawdustgave the best for number of individu, number of type and population densityof soil macrofauna. The application of 10 kg/plant palm oil empty fruit bunch showed the best results for increasing of plant height, increasing number of fronds, increasing of fronds length and increasing of leaves. Organic matter which showed the best result for soil macrofauna was not show the best results for oil palm growth.   Keywords : organic matters, soil macrofauna, palm oil